Analisis Manajemen Resiko pada UMKM Warung Kelontong - Syahanra, Ardiva Zuniar; Khoeri, Musodik (Jurnal Serambi Ekonomi dan Bisnis, 2024)
Risk analysis in grocery stores is important to ensure business sustainability amidst intense competition and economic challenges. This research aims to identify and analyze various risks faced by MSME grocery stalls, such as operational, financial and external risks. The approach used is a qualitative descriptive method with direct interviews with business owners and observation of operational activities. The analysis results show that the main risks include limited capital, fluctuations in prices of basic commodities, competition with modern minimarkets, and dependence on certain suppliers. To overcome this risk, mitigation strategies are needed such as product diversification, more effective financial management, and developing relationships with customers. It is hoped that this study can serve as a guide for MSME grocery store operators in increasing their competitiveness and business sustainability